Environmental Management In Times Of Pandemic. A Bibliometric Study - Arias Chavez, Dennis (2023)
The study aims to characreríze the global scientific production on environmental management ar the global level in the Scopus and Web of Science, between the months ofJanuary 10'.W to March 2022. A retrospective descriptive bibliometric analysis was carried out.1133 documents from the Web of database were analyzed. Science and 1687 from scopus, drawn from 565 and 771 sources respectively. Regarding the number of authors, Scopus presents 6067 and Web of Science, 4043. The rate of collaboration berween authors is slightly lower in Web of Science (3.82) compared to 3.95 from Scopus. Toe most cited article is "Green innovation and environmental performance: Toe role of green t:ransformational leadership and green human resource management ", the author with the most papers on the subject is Yi Zhang, IOP Conference Series: Earth And Environmental magazine Science stands out as the médium with the largest number of publicatíons related to environmental management, the type of scientific document that stands out the most is the original arricle, as for the country with the largest munber of publications on environmental managemenr, China stands out. With regard to collaboration between countries, China and Pakistan stand out in the case of Web of Science and China and the United States in the case of Scopus . It is concluded that, in recent years. scientific production on environmental management has shown an accelerated increase motivated by the dramatic changes generated by the COVID-19 pandemic.